lncRNA AWPPH promotes the migration and invasion of glioma cells by activating the TGF-β pathway - Dai, Bin (Oncol Lett, 2019)
The long noncoding RNA (lncRNA) AWPPH, also termed microRNA-4435-2HG, has been associated with the poor prognosis of patients with hepatocellular carcinoma (HCC), and has been demonstrated to promote the progression of HCC and bladder cancer. The present study aimed to investigate the role of lncRNA AWPPH in glioma. The expression levels of AWPPH in tumor tissues obtained from patients with glioma and in plasma samples obtained from patients with glioma and healthy controls were detected by reverse transcription-quantitative polymerase chain reaction. The plasma levels of transforming growth factor (TGF)-β1 were measured by an enzyme-linked immunosorbent assay. An AWPPH expression vector was transfected into human glioma cell lines. Subsequently, cancer cell migration and invasion were assessed by Transwell migration and invasion assays, respectively. The expression of TGF-β1 in the transfected-glioma cells was detected by western blot analysis. It was identified that AWPPH expression levels in tumor tissues were higher in patients with metastatic glioma; however, no significant differences in AWPPH expression were revealed between patients with different tumor sizes. The plasma levels of AWPPH were positively correlated with the plasma levels of TGF-β1 in patients with glioma but not in healthy controls. In addition, AWPPH overexpression enhanced cancer cell migration and invasion, and upregulated TGF-β1 expression. Treatment with TGF-β1 demonstrated no significant effect on AWPPH expression; however, a TGF-β inhibitor attenuated the effects of AWPPH overexpression on cell migration and invasion. Therefore, the present study proposed that AWPPH may promote the migration and invasion of glioma cells by activating the TGF-β pathway.